Involved node radiation therapy in the combined modality treatment for early-stage Hodgkin lymphoma: Analysis of relapse location and long-term outcome. (September 2020) - Nielsen, Karin; Maraldo, Maja Vestmoe; Berthelsen, Anne Kiil; Loft, Annika; de Nully Brown, Peter; Vogelius, Ivan Richter; Petersen, Peter Meidahl; Specht, Lena
Highlights: Relapses in early-stage Hodgkin lymphoma are uncommon. Relapses rarely occur in irradiated lymph nodes. Without radiation relapses occur preferentially in initially involved lymph nodes. All initially involved lymph nodes should be irradiated. Abstract: Background and purpose: Involved node radiation therapy (INRT) in the combined modality treatment for early-stage Hodgkin lymphoma (ESHL) has reduced the irradiated volume dramatically. Limiting the irradiated volume further based on initial disease bulk, 18F-fluoro-deoxy-glucose (FDG)-avidity, or residual computed tomography (CT) abnormality after chemotherapy seems attractive. In a cohort of patients treated with INRT a meticulous pattern-of-relapse analysis was performed to examine these options. Material and methods: Patients treated for ESHL in our institution from 2005 to 2014 who achieved complete remission with chemotherapy were included. Patient characteristics, treatment details and clinical outcome were registered. For relapsed patients, rigid co-registration of the positron emission tomography/computed tomography-scans from the time of diagnosis and at relapse was done to visually assess the relapse location relative to initial involvement and, if irradiated, the irradiated volume. Size and maximum Standardized Uptake Value of the initial node(s) with later relapse, and residual CT abnormalities after chemotherapy in those locations were measured. Results: We included 182 patients. Twelve (6.6%) patients relapsed, five in previously involved nodes (two irradiated, three not irradiated). Relapses did not occur preferentially in initially bulky disease, in lymph node(s) with the highest FDG-uptake, or in residual CT abnormalities after chemotherapy. Conclusions: Modern treatment with brief chemotherapy and limited radiotherapy provides excellent long-term disease control in ESHL. Neither bulk, high FDG-uptake, nor residual CT abnormality after chemotherapy could predict initially involved lymph nodes with a high risk of relapse.